2020
DOI: 10.48550/arxiv.2008.03410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OCMR (v1.0)--Open-Access Multi-Coil k-Space Dataset for Cardiovascular Magnetic Resonance Imaging

Abstract: Cardiovascular MRI (CMR) is a non-invasive imaging modality that provides excellent softtissue contrast without the use of ionizing radiation. Physiological motions and limited speed of MRI data acquisition necessitate development of accelerated methods, which typically rely on undersampling. Recovering diagnostic quality CMR images from highly undersampled data has been an active area of research. Recently, several data acquisition and processing methods have been proposed to accelerate CMR. The availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Experiments were performed by retrospectively undersampling fully sampled datasets in six dynamic MRI applications: (i) multi parameter brain sequence (brain) [45], (ii) free breathing un-gated cardiac perfusion (cardiac-fb) [46] (this had both perfusion dynamics and motion dynamics due to cardiac and breathing motion), (iii) free breathing PINCAT perfusion phantom (PINCAT) [4], [9] (containing dynamics due to perfusion uptake in the heart as well as heavy breathing motion), (iv) a short 59-frame speech sequence acquired on a University of Iowa volunteer speaking slowly (short-speech), (v) one breath-held cardiac sequence from the OCMR database [47] (cardiac-cine), and (vi) a high temporal resolution (2048frame) but low spatial resolution speech sequence acquired at the University of Iowa on a healthy volunteer (long-speech). Details of these datasets are provided in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were performed by retrospectively undersampling fully sampled datasets in six dynamic MRI applications: (i) multi parameter brain sequence (brain) [45], (ii) free breathing un-gated cardiac perfusion (cardiac-fb) [46] (this had both perfusion dynamics and motion dynamics due to cardiac and breathing motion), (iii) free breathing PINCAT perfusion phantom (PINCAT) [4], [9] (containing dynamics due to perfusion uptake in the heart as well as heavy breathing motion), (iv) a short 59-frame speech sequence acquired on a University of Iowa volunteer speaking slowly (short-speech), (v) one breath-held cardiac sequence from the OCMR database [47] (cardiac-cine), and (vi) a high temporal resolution (2048frame) but low spatial resolution speech sequence acquired at the University of Iowa on a healthy volunteer (long-speech). Details of these datasets are provided in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed DTLR-Net brings a new perspective of exploiting the tensor low-rank prior by enforcing a lowrank constraint on the feature domain learned by the neural network. Reconstruction results on a prospective Cine MR dataset (real-time OCMR [13]) demonstrate the superior performance of the proposed TLR-Net over state-of-art methods.…”
Section: Introductionmentioning
confidence: 94%
“…Open-access Multi-coil k-space Dataset for Cardiovascular Magnetic Resonance Imaging dataset (OCMR) 5 [33] is an open-access dataset that provides multi-coil k-space data for VII. COMMON PITFALLS Previous studies have shown several benefits of deep neural network based techniques over conventional constrained reconstruction using specified regularisers.…”
Section: Cardiac Mri (Eg Ocmr Dataset)mentioning
confidence: 99%